2016
DOI: 10.3390/ijms17111827
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Everolimus in an In Vitro Model of Triple Negative Breast Cancer and Osteoclasts

Abstract: Metastatic bone disease has a major impact on morbidity of breast cancer (BC) patients. Alterations in mTOR signaling are involved both in cancer progression and in osteoclast differentiation. The purpose of this study was to assess the role of mTOR inhibitor Everolimus (Eve) on osteoclastogenesis induced by triple negative BC cells. To this aim, we developed an in vitro human model of osteoclastogenesis from peripheral blood monocytes co-cultured with the triple negative SCP2 and the hormonal receptor positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Osteoclasts are not the only TRAP-positive polinucleated cells of a monocytic origin. In a previous work we confirmed that the osteoclast cell-like cells positive to TRAP are real osteoclasts, as we observed the presence of two specific osteoclast markers, i.e., Actin ring and calcitonin receptor (CTR), both in the negative control and in the differentiation medium (DM) condition [ 12 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Osteoclasts are not the only TRAP-positive polinucleated cells of a monocytic origin. In a previous work we confirmed that the osteoclast cell-like cells positive to TRAP are real osteoclasts, as we observed the presence of two specific osteoclast markers, i.e., Actin ring and calcitonin receptor (CTR), both in the negative control and in the differentiation medium (DM) condition [ 12 ].…”
Section: Resultssupporting
confidence: 75%
“…Human pre-osteoclasts were generated from PBMC, following a previously established protocol with some modifications [ 12 ]. Briefly, PBMC of healthy donors who had given their written informed consent were separated by Ficoll density centrifugation (Lymphosep, Biowest, NuaillĂ©, France), counted and seeded in αMEM medium (Lonza) supplemented with 10% FBS, 1% penicillin/streptomycin, 1% glutamine (referred to as complete αMEM), in 24-well plates at a density of 750,000 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional medical regimens were discussed. Bisphosphonates in combination with sirolimus have suggested a synergistic effect when utilized in complicated lymphatic anomalies of the bone (GLA and Gorham Stout Disease) 11,12 and in the treatment of malignancies with metastatic bone disease 16 . Given his bone involvement and continued thrombocytopenia, around 18 months after diagnosis the patient was initiated on a trial of zoledronate (0.025 mg/kg intravenously monthly for 6 months, then every 3 months for 1 year).…”
Section: Treatmentsmentioning
confidence: 99%
“…Despite these considerations, a recent study supports our observations of everolimus as being an inhibitor of osteoclastogenesis. When investigating the effects of everolimus on the osteoclastogenesis of peripheral blood monocytes in a coculture model with the triple-negative breast cancer cell line SCP2, everolimus was effective at inhibiting osteoclastogenesis induced by SCP2-derived factors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%